2021
DOI: 10.2147/eb.s307551
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Modifications in Glaucoma and Macular Degeneration: Analysis of Current Evidence in Literature and Their Implications on Therapeutic Perspectives

Abstract: Glaucoma and macular degeneration are leading causes of irreversible blindness, significantly compromising the quality of life and having a high economic and social impact. Promising therapeutic approaches aimed at regenerating or bypassing the damaged anatomical-functional components are currently under development: these approaches have generated great expectations, but to be effective require a visual network that, despite the pathology, maintains its integrity up to the higher brain areas. In the light of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 126 publications
(206 reference statements)
0
4
0
Order By: Relevance
“… 31 , 32 The metabolic and neurotrophic imbalances in retinal tissues can be related to the morphological and functional changes along the visual pathway and in numerous brain areas outside the visual pathway known to affect the CNS in glaucoma. 7 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 31 , 32 The metabolic and neurotrophic imbalances in retinal tissues can be related to the morphological and functional changes along the visual pathway and in numerous brain areas outside the visual pathway known to affect the CNS in glaucoma. 7 …”
Section: Discussionmentioning
confidence: 99%
“…Current research advancing this understanding links glaucoma to degeneration of the central nervous system (CNS), moving it away from being considered just a traditional eye disease. A recent review assessing the morphological and functional changes affecting the CNS in glaucoma 7 reported structural alterations along the visual pathway and in numerous cognitive functions outside the visual pathway, such as for visual memory, working memory, attention, and motor coordination. These observations suggest that independent mechanisms of neurodegeneration in glaucoma are potentially affecting neural tissues in addition to the known anterograde and/or retrograde neuronal degeneration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of these studies showed that a decrease of volume with structural micro-alterations, which especially affects the white matter, is to show the neurodegenerative character of glaucoma with implications for future therapies [ 41 , 59 ], but also to emphasize the cerebral modifications of the cerebral networks in glaucoma [ 43 , 44 ].…”
Section: Cerebral Neuroimaging In Glaucomamentioning
confidence: 99%
“…The possibility that Alzheimer's disease (AD) and primary open angle glaucoma (POAG) may share a common underlying aetiology has been increasingly realised over recent years [1]. This stems not only from their obvious similarities as chronic neurodegenerative diseases associated with aging, but also from the results of numerous epidemiological [2,3], pathological [4][5][6] and vascular studies [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%